Influence of odd–even effect and intermolecular interactions in 2D molecular layers of bisamide organogelators. Issue 61 (15th October 2018) - Kocasoy, Volga; Dedeoglu, Burcu; Demir-Ordu, Oznur; Aviyente, Viktorya
Abstract : Our computational results rationalize the factors that affect the molecular self-assembly of bisamides and its role on gelation. Abstract : Organogelators have a wide range of use in everyday life including drug delivery and controlled release, surface coating and paper industry. In this study, a series of model bisamides have been analyzed as potential organogelators. These molecules are connected by odd and even numbered methylene units ( n ) in length ranging from 2 to 9. By constructing layers of those molecules along the growth direction we provide an insight into the self-assembly process. A complete systematic analysis of the computational results with B3LYP/6-311+G** suggests that the self-assembly of these potential organogelators is influenced by the odd–even effect, the relative direction of amide carbonyl groups, the bridging spacer chain length and the presence of a chiral alpha carbon. The aforementioned factors alter the strength of the intermolecular hydrogen bonds as well as the van der Waals interactions, which in turn may affect the self-assembly process of gelation and result in the formation of aggregates with different shapes. It is found that molecules with short central chains have an energetic preference for antiparallel arrangement over their parallel analogues as a result of stronger hydrogen bonding interactions. As the central chain elongates, the free energy difference between antiparallel and parallel structures decreases suggesting a compromise between hydrogen bonding and van der Waals interactions. The complete structural analysis suggests ribbon-like structures for achiral even-antiparallel and woven-like structures for odd-parallel systems, respectively. Upon creation of asymmetry on the alpha carbon, a twisted ribbon-like and a coiled coil-like structure are observed for even and odd systems, respectively. Our computational results are in accordance with the experimental results and provide an insight into the self-assembly of layers of bisamides.